The anatomical connections of the macaque monkey orbitofrontal cortex. A review - Cavada, Carmen; Compañy, Teresa; Tejedor, Jaime; Cruz-Rizzolo, Roelf J. [UNESP]; Reinoso-Suárez, Fernando (Oxford University Press (OUP), 2000)
The orbitofrontal cortex (OfC) is a heterogeneous prefrontal sector selectively connected with a wide constellation of other prefrontal, limbic, sensory and premotor areas. Among the limbic cortical connections, the ones with the bippocampus and parabippocampal cortex are particularly salient. Sensory cortices connected with the OfC include areas involved in olfactory, gustatory, somatosensory, auditory and visual processing. Subcortical structures with prominent OfC connections include the amygdala, numerous thalamic nuclei, the striatum, hypothalamus, periaqueductal gray matter, and biochemically specific cell groups in the basal forebrain and brainstem. Architectonic and connectional evidence supports parcellation of the OfC. The rostrally placed isocortical sector is mainly connected with isocortical areas, including sensory areas of the auditory, somatic and visual modalities, whereas the caudal non-isocortical sector is principally connected with non-isocortical areas, and, in the sensory domain, with olfactory and gustatory areas. The connections of the isocortical and non- isocortical orbital sectors with the amygdala, thalamus, striatum, hypotbalamus and periaqueductal gray matter are also specific. The medial sector of the OfC is selectively connected with the bippocampus, posterior parabippocampal cortex, posterior cingulate and retrosplenial areas, and area prostriata, while the lateral orbitofrontal sector is the most heavily connected with sensory areas of the gustatory, somatic and visual modalities, with premotor regions, and with the amygdala.
Keywords: animal tissue; brain function; brain mapping; controlled study; monkey; nonhuman; orbital cortex; priority journal; sensory cortex; sensory nerve; thalamus; Animals; Female; Frontal Lobe; Limbic System; Macaca nemestrina; Male; Neural Pathways